2006
DOI: 10.1148/radiol.2402050107
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Risk of False-Positive Screening Results and Subsequent Biopsy as a Function of Mammography Use

Abstract: Prompt annual attendance for mammographic screening reduces the occurrence of false-positive mammographic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…Christiansen (2000) found a FP probability of 22% after five screening mammograms under biennial screening for an intermediate-risk woman and median radiologist (15), compared to estimates for our population of 38-40%. Studies of benign biopsy have found a probability of 8-9% after 10 screening rounds (12,13), which are similar to our estimate. Based on our review, we believe ours is the first study to incorporate covariate effects and variation among radiologists into estimates of cumulative FP biopsy recommendation rates.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Christiansen (2000) found a FP probability of 22% after five screening mammograms under biennial screening for an intermediate-risk woman and median radiologist (15), compared to estimates for our population of 38-40%. Studies of benign biopsy have found a probability of 8-9% after 10 screening rounds (12,13), which are similar to our estimate. Based on our review, we believe ours is the first study to incorporate covariate effects and variation among radiologists into estimates of cumulative FP biopsy recommendation rates.…”
Section: Discussionsupporting
confidence: 91%
“…They will undergo 17 examinations if they start biennial screening at age 40, 24 if they start annual screening at age 50, and 34 if they start annual screening at age 40. Estimates of the probability that a woman will experience at least one FP recall after 10 screening examinations range from 29% to 77% (10)(11)(12), and are about 8-9% for benign biopsy (12,13). These estimates, however, are based on extrapolations, are limited by statistical methodology that assumes women participating in multiple screening rounds are representative of all women recommended for screening, and do not take into account factors shown in prior studies to be associated with wide variability in FP rates, such as radiologist recall rates (14)(15)(16)(17) and patient age, breast density, hormone therapy use, and screening interval (6,15,18).…”
Section: Introductionmentioning
confidence: 99%
“…Our results confirm the previous observation by Blanchard et al [6] that the majority of false-positive findings occur early in a woman's screening experience. The overall PPV of BI-RADS 3, 4, and 5 in women under aged 50 and below in this study was 9.1 versus 41.6% in women aged 50 and above in the comparison group.…”
Section: Discussionsupporting
confidence: 92%
“…Mammography is the current gold standard, but can have false negative rates of up to 20% [26]. The diagnosis of breast cancer relies on the histological examination of tissue biopsies, or cytology of fine-needle aspirates, which are both invasive procedures.…”
Section: Introductionmentioning
confidence: 99%